High-power radiofrequency quadrupoles: Review of recent developments, common problems, and solutions - Yuan He; Wei-ping Dou; Chen-xing Li; Zhi-jun Wang; Tian-cai Jiang; Zhou-li Zhang; Lie-peng Sun; Zheng Gao; Xiao-feng Jin; Gui-rong Huang; Ran Huang; Feng-feng Wang; et al. (Physical Review Accelerators and Beams)
The RFQ accelerator, often the initial rf component in a hadron accelerator, focuses, bunches, and accelerates the beam from several keV to MeV across a several-meter quadrupole channel. Due to the significant application potential of high-power RFQs, research efforts have grown substantially in recent years. This paper reviews global advancements in high-power RFQ technology. The stable operation of these high-power RFQs faces many design challenges and technological limitations. The experiences and lessons learned from the recent design, fabrication, high-power rf conditioning, and beam commissioning processes have been summarized. Key issues related to thermal effects, multipacting, sparking, stability, and frequency detuning in the components of the RFQ system are presented, and the proposed solutions are discussed.